(untitled) (Anclajes, 2023)
The place of Antonio Argerich, author of ¿Inocentes o culpables? (1884), in the emergence of the national novel and in the context of the controversy surrounding naturalism, has been widely studied. His role as a critic, meanwhile, has received less attention. Based on extensive archival work, in this article we recover and analyze a long series of interventions from 1882 to 1886. In addition to reconstructing the conditions of production of the author’s well-known dissertation on naturalism, the article’s main objective is the recovery and study of a letter by Émile Zola to Argerich, from its background and consequences to the complex textual network that emerged from it. In this way, we study the inflections of the key role that Argerich played as a critic, defender, and promoter of naturalism, while we reconsider certain distinctive features of this central debate in the literary criticism of the period.